Laporan Kasus Serial : Penderita Appendisitis Pada Anak Dengan Gejala Menyerupai Gastroenteritis Akut Di RS Swasta Tipe C, Kota Tangerang 2018-2020 - Hasan, Fahad (Health Information : Jurnal Penelitian, 2023)
Appendicitis is one of the acute abdominal emergency cases in children requiring surgery. The age group is most often found in pre-school age or above. In general, appendicitis is not associated with gastroenteritis, but we found some cases of atypical appendicitis with predominant symptoms of diarrhea, nausea and vomiting. In contrast to adults, the pathogenesis of appendicitis in children is known to be associated with terminal ileal lymphoid hyperplasia, so it is theoretically possible that appendicitis can occur as a sequela after gastroenteritis. The younger the child, the more difficult it is to take a history and evaluate the results of a physical examination. In some cases, the dominant symptom may be diarrhea, severe nausea and vomiting so that the patient is delayed in getting proper treatment because it is considered as gastroenteritis. Delay in diagnosing appendicitis will cause complications such as peri-appendicular abscess, peritonitis and sepsis. The misdiagnosis rate in children aged 2-12 years is about 28-57% and is almost 100% in children younger than 2 years. The purpose of this study was to obtain data on the characteristics of patients with appendicitis accompanied by symptoms of gastroenteritis such as nausea, vomiting and diarrhea in children aged 0-14 years. This study is a review of case series reports using patient medical record data at a type C private hospital in Tangerang City in the 2018-2020 period. Found 4 cases of appendicitis with atypical symptoms resembling gastroenteritis in the form of vomiting and diarrhea > 10 times per day. The four patients came to the ER with two of them being treated by pediatricians first. These two patients received surgical intervention > 24 hours after being admitted with surgical findings of perforated appendicitis accompanied by intra-abdominal pus contamination. The length of stay of the four patients > 3 days. Atypical symptoms of appendicitis that resemble gastroenteritis in children can cause delays in making a diagnosis so that there is a risk of complications of appendicitis. Every clinician should suspect the possibility of appendicitis when he sees a pediatric patient with symptoms of gastroenteritis accompanied by accompanying findings including abdominal pain that gets worse or worsens after 24 hours despite medical therapy.